A facile microwave-hydrothermal synthesis of fluorescent carbon quantum dots from bamboo tar and their application. Issue 24 (9th June 2017) - Liang, Qian; Wang, Yulin; Lin, Fengcai; Jiang, Maosheng; Li, Pengfei; Huang, Biao
Abstract : A simple and rapid approach that can effectively convert bamboo tar into carbon quantum dots (CQDs) was developed and this kind of CQD was adopted for the selective detection of 2, 4, 6-trinitrophenol (TNP). Abstract : Bamboo tar is a water-insoluble semi-solid by-product generated from bamboo charcoal processing. A simple and rapid method to convert bamboo tar into carbon quantum dots (CQDs) was developed by a microwave-hydrothermal route, which was applied to the sensitive and selective detection of 2, 4, 6-trinitrophenol (TNP) under acidic conditions. The obtained CQDs were characterized by transmission electron microscopy (TEM), X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS) and fluorescence spectroscopy. The results indicate that the CQDs emit strong blue fluorescence centered at 450 nm under the excitation band of 380 nm with a high quantum yield of 19.3%. A sensitive approach has been developed for the detection of TNP in the range of 0.2–20 μM with a detection limit of 33 nM based on the fluorescence resonance energy transfer (FRET), inner filter effect (IFE) and electron transfer (ET) between CQDs and TNP. This approach is highly selective and suitable for TNP analysis in natural water samples.